2020
DOI: 10.1108/ebr-08-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Systematically reviewing servant leadership

Abstract: Purpose The purpose of this paper is to provide a comprehensive overview of the literature concerning servant leadership. The paper identifies the existing themes present within the servant leadership literature. This allows it to determine where the research concerning servant leadership lies at present and make recommendations as to further potential areas for research. It further identifies the skills necessary for servant leadership. Design/methodology/approach The paper follows a rigorous three-step sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 93 publications
2
56
0
3
Order By: Relevance
“…As a leadership style, servant leadership is principled, selfless and anthropocentric (Sendjaya and Sarros, 2002), integrating values of integrity, humility and self-awareness, which are all primary components of a healthy working environment (Page and Wong, 2000). A comprehensive literature review found that the necessary skills for servant leadership are empathy, listening, communication and trust (Mcquade et al, 2021).…”
Section: Servant Leadershipmentioning
confidence: 99%
See 4 more Smart Citations
“…As a leadership style, servant leadership is principled, selfless and anthropocentric (Sendjaya and Sarros, 2002), integrating values of integrity, humility and self-awareness, which are all primary components of a healthy working environment (Page and Wong, 2000). A comprehensive literature review found that the necessary skills for servant leadership are empathy, listening, communication and trust (Mcquade et al, 2021).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Servant leadership has been linked to several individual, team and organisational outcomes. At the individual level, the most saturated area of research pertains to performance, and it is generally accepted that servant leadership improves employee job performance (for a comprehensive review, see Mcquade et al, 2021). Building on social exchange theory, it has been found that servant leadership reduces turnover intentions (Jang and Kandampully, 2018).…”
Section: Servant Leadershipmentioning
confidence: 99%
See 3 more Smart Citations